Faktor-faktor yang mempengaruhi kepuasan pelanggan terhadap kualiti perkhidmatan zakat: Kajian kes Pejabat Zakat Daerah Baling (PZDB), Kedah - Abidah, Ab Kadir (2015)
The purpose of this study was to investigate the relationship between customer satisfaction and service quality management charity in the state. The study was conducted based on demographic and six dimensions of quality of service reliability, assurance, compliance, tangible, empathy and responsiveness. Respondents for this survey were customers Pejabat Zakat Daerah Baling (PZDB), Kedah and of 280 questionnaires were distributed to the customers. While the design of this study is a survey with the quantitative approach. The questionnaire used as an instrument to obtain data for this study. Data were analyzed using the program Statistical Package for Social Science (SPSS) version 19. The analysis used in this research is descriptive analysis and inferential analysis comprising, t-test, mean test, one-way analysis of variance (ANOVA), Pearson and regression. The study showed that the relationship between women customers and male customers are not significant. The majority of customers Pejabat Zakat Daerah Baling (PZDB) consist of those in the age group 40 to 60 years, which covers 48.1% of the total population. Customers who have married are majority of customers Pejabat Zakat Daerah Baling (PZDB) of 71.1%. Most customers Pejabat Zakat Daerah Baling (PZDB) have secondary school education by 39.5% and the public sectors were the most used services Pejabat Zakat Daerah Baling (PZDB) of 42.1%. Customers of Pejabat Zakat Daerah Baling (PZDB) also consists of those earning less than RM1,000 by 42.1%. The mean score for overall dimensions of service quality and customer satisfaction is high. Pearson correlation test results showed that all six dimensions of service quality have a positive significant relationship with customer satisfaction. Regression analysis showed that adherence factor, empathy and responsiveness is the most critical factor to the customer satisfaction. In sum, customers are satisfied with the quality of services delivered by the Pejabat Zakat Daerah Baling (PZDB)